Indicadores de sustentabilidade: análise da aplicabilidade da NBR ISO 37120:2017 sob a perspectiva da Engenharia Urbana - Almeida, Suise Carolina Carmelo de (2019)
Given the changes that have been occurring in urban planning in the last decades, due to the global growth of ecological awareness, it is necessary to observe the actions that governments have taken to achieve the goal of making cities more sustainable and analyze their effectiveness. Brazil is inserted in this context through the adoption of some practices aligned with the objectives of Agenda 2030 as a goal for the coming years. Some methodologies are being used to evaluate and monitor urban sustainability, these methodologies serve as a guideline for governance in order to, through the use of indicators, obtain sustainability parameters in urban development by measuring how much progress is made in this direction or the level of sustainability already achieved, such as the Sustainable Development Indicators, the Green Blue Municipality (in the State of São Paulo), the Sustainable Cities Program, among others, all of which are considered insufficient to contemplate Brazilian diversities. In January 2017 a new methodology for measuring sustainability was proposed, the Brazilian Association of Technical Standards (ABNT) published the NBR ISO 37120/2017 - Sustainable development of communities - Indicators for urban services and quality of life, this is a Translation of ISO 37120/2014 - Sustainable development of communities - Indicators for city services and quality of life, with some explanatory notes. It is understood that this norm came in response to the Brazilian need to have a normative document that guides the control and monitoring of the progress of cities in achieving sustainable development, it determines and guides the application of a set of indicators that aim to measure the performance of urban services and the quality of life of the population, and also serves to leverage the discussion of sustainability in the country, attributing to the cities a conscious image regarding their relationship with the environment, as well as seeking to bring to the population a new culture environmental awareness. The aim of this study is to analyze, through case studies carried out in two medium-sized cities in the state of São Paulo, São José do Rio Preto and Araraquara, the applicability of this norm from the point of view of Urban Engineering, , based only on the indicators of the standard that relate directly to Urban Engineering, making a critical approach on these indicators with the help of an Indicators Dashboard and later, with the obtaining of these data, apply the Urban Benchmarking technique between the two cities . The present study also analyzes aspects of its applicability to the Brazilian reality, due to the need to overcome some incompatibilities in terms of parameterization of the data collection and methodologies to obtain the indicators. As results obtained in this research, it was observed that these indicators, if properly applied, could represent an important standardized collection of historical series of urban data that will bring much aggregated knowledge to be explored in municipal governance. The comparative vision of the standard complements its potential as a management tool and can provide a global picture of the situation of local and worldwide sustainability. It was concluded that despite the contributions generated with the adoption of this and other methodologies, there are still challenges to be overcome in the construction of indicators of urban sustainability in order to simultaneously add aspects considered essential to promote changes in society and subsidize public policy decisions, a problem complicated by the lack of urban management infrastructure in the municipalities, which generates the need for adaptations in obtaining the indicators due to the difficulty of producing standardized data.